Antimicrobial Potential of Phenolic Compounds from Seidlitzia Rosmarinus and Ziziphus Spina-Christi against Trichomonas Vaginalis: A Natural Alternative to Conventional Therapy - Hamood, Nibras abud al Aziz (Journal of Science in Medicine and Life, 2025)
This study investigates the presence of Trichomonas vaginalis among women visiting Samarra General Hospital and private clinics. The parasite was successfully cultured in TYM medium, with the logarithmic growth phase observed at 48 hours. Phenolic compounds were extracted from Seidlitzia rosmarinus and Ziziphus spina-christi leaves and identified using High-Performance Liquid Chromatography (HPLC). Results showed that phenolic extracts from both plants exhibited significant inhibitory effects on parasite growth, with varying efficacy based on concentration and exposure time. Kaempferol acid and Caffeic acid were identified as key phenolic compounds, contributing to the antimicrobial, antioxidant, and anti-inflammatory properties observed. These findings highlight the potential of plant-derived phenolic compounds as alternative treatments for Trichomonas vaginalis infections, offering a promising avenue for further research.